SISTEM INFORMASI PENJUALAN MAKANAN RINGAN (SIPMAR) BERBASIS WEB PADA R & R DENGAN PHP DAN MYSQL: System, Information, Sales, Web, PHP, MySql - Nilawati; Riswan; Fachri (LP2M Universitas Nurdin Hamzah, 2023)
The research aims to build a sales information system on the R&R based on the web. The system was developed using the PHP programming language using MySQL as a database. The method of data collection is done by way of interviews, observation, and coupled with a study of the library which has a connection with the problems faced. While the research method used is the descriptive qualitative research with the Waterfall model development system. From research conducted, found problems such as; 1) Manual recording is not neat, 2) not regularly structured sales transactions, and 3) Often lost transaction notes , resulting in difficulties in recording transactions and also errors in recording the end of month reports. The effort to solve this problem is by creating a web-based sales information system using MySQL